Hubungan antara Partner Support dengan Resiliensi pada Wanita yang Mengalami Abortus Spontanea - Natasya, Shahdifa; Suharsono, Yudi; Saraswati, Putri (Fakultas Psikologi, 2019)
Women who experience spontaneous abortion tend to experience psychological disorders such as stress, anxiety, and emotional disturbances. When facing this event, women are expected to have good resilience to deal with these disorders. For women who have experienced a miscarriage, support from a partner plays an important role in helping the woman to be resilient from the stressor due to a miscarriage. This study is a correlational study to determine the relationship between partner support and resilience in women who experience spontaneous abortion. The subjects involved in this study were 46 people taken by the snowball sampling technique. The process of collecting data uses a scale of partner support and scale of resilience (CD-RISC) and analyzed using product moment correlation. The results showed that there was a significant correlation between partner support and resilience in women who experienced spontaneous abortion (r = 0.413; p = 0.004 <0.05), and R square of 0.170 (17%), indicating that 17 % resilience is influenced by partner support and 83% is influenced by other variables.